PREGNANCY AND PREVENTION OF NEURAL TUBE DEFECTS ASSOCIATION (PROSPECTIVE STUDY) - Dr. Aaeda Mohammed Ameen Yousif; Dr. Fatima Farhan Mamakan (Scholar Express Journals, 2022)
Neural tube defects (NTDs) are the second most common congenital malformations of humans, characterized by impaired development of the central nervous system. Even though the etiology of most birth defects remains undetermined, genetic and environmental risk factors in the background of NTDs have been identified and extensively reported. On top of genetic and nutritional risks which include mutations in both coding and non-coding regions and maternal folate status, respectively, recent years have seen a rise in the identification of a variety of teratogens that could be implicated in NTD development. These include polycyclic aromatic hydrocarbons, arsenic, pesticides, maternal hyperthermia and antibiotics as well as pain and seizure medication. With an increase in understanding of teratogens leading to NTD formation, preventative and treatment approaches have witnessed great advances throughout the years. While the most common preventative approach includes folic acid food fortification as well as suggested inositol supplementation, treatment and management approaches differ greatly depending on the developmental stage and the site of the lesion and include prenatal surgery, stem cell transplantation and postnatal surgery. Because NTDs still represent a large health and financial burden for the patient and society as a whole, it is crucial to investigate potential risk factors and develop novel approaches in order to fully prevent this category of disorders
Keywords: neural tube development; neural tube defects; congenital malformations; spina bifida